The role of Lazismu on entrepreneurship empowerment program for the poor - Sutrisno, Sutrisno; Haron, Razali; Rozikan, Rozikan (Atlantis Press, 2021)
Zakat institutions play a strategic role in the management of zakat funds and other social funds in order to carry out the law's mandate and alleviate poverty through various programs. Meanwhile, zakat institutions are responsible for the majority of poverty alleviation through consumptive programs. Based on the results of the Lazismu National Zakat Institute's management, it has obtained the largest zakat fund acquisition achievement nationally in 2020. This study aims to explore in depth how zakat programs are created, managed, and implemented for economic empowerment of the poor in Lazismu by interviewing, which has been successful in creating and implementing economic empowerment programs for zakat recipients throughout Indonesia. This study took a qualitative approach, with data collected through interviews. The results Lazismu's role through the poor community empowerment program is carried out in several stages, starting from the preparation of the strategic plan before the program is implemented, determining the type of program, implementation, evaluation and mentoring. The program of Lazismu is in the form of rising farmers, MSMEs, livestock, capital assistance for Islamic microfinance institutions in accordance with the theory of raising the spirit of entrepreneurship and smart goals. Overall economic empowerment program carried out by Lazismu, in general, it went well and smoothly according to the planned target. In addition, the economic empowerment program carried out by Lazismu has succeeded in converting zakat recipients into zakat providers by 50% of the total economic empowerment programs carried out.